(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
This research is devoted to studying the role of graphene oxide (GO) in improving the physical and mechanical properties of cement-based composite materials. In the experiment, the effect of GO at a dosage of 0.05% by weight of cement on the hydration process was analyzed. The results showed that the addition of GO increases the density of concrete and can reduce concrete cracking by up to 35%. The article also provides information on the environmental efficiency of nano-concrete.